Oxidation of short and medium chain C2-C8 fatty acids in Sprague-Dawley rat colonocytes. - Jørgensen, J R (1997)
BACKGROUND: The predominant colonic short chain fatty acids, acetate, propionate, and butyrate, are oxidised into CO2 in colonocytes from rat and humans in the preferred order of butyrate (C4) > propionate (C3) > acetate (C2)- hence butyrate is considered to be the principal oxidative substrate for colonocytes. AIMS: To compare colonocyte oxidation of valerate (C5), hexanoate (C6), and octanoate (C8) with that of butyrate. METHODS: Isolated rat colonocytes were incubated in the presence of a concentration range of 1-14C labelled C2-C8 fatty acids. Oxidation rates were obtained by quantifying the production of 14CO2, and Vmax (maximum velocity) and K(m) (Michaelis-Menten constant) were calculated by computer fitting of the data to a Michaelis-Menten plot. RESULTS: The K(m) value of acetate (0.56 (SEM 0.02) mmol/l) was about fourfold higher than the K(m) of butyrate (0.13 (0.01) mmol/l), whereas the K(m) values of valerate (0.19 (0.01) mmol/l), hexanoate (0.19 (0.01) mmol/l), and octanoate (0.16 (0.01) mmol/l) were of the same order of magnitude as the K(m) of butyrate. Acetate did not influence butyrate oxidation, whereas butyrate strongly inhibited the oxidation of acetate. By contrast, valerate, hexanoate, and octanoate inhibited colonocyte oxidation of butyrate equally or more than the reverse inhibitory effect of butyrate on valerate, hexanoate, and octanoate oxidation. The maximum rates of ATP production were in the order of valerate > octanoate = hexanoate > butyrate > acetate (28.47 (0.70), 21.78 (0.75), 21.33 (0.78), 16.12 (0.49), 9.09 (0.34) (mumol/min/g) respectively). CONCLUSIONS: Valerate, hexanoate, and octanoate seem to be excellent substrates for colonocyte oxidation, similar to butyrate. These results may influence the choice of fatty acid composition in enemas used for treatment of patients in whom deficient colonocyte oxidation is suspected-for example, patients with ulcerative colitis and diversion colitis.